Molecular Detection of Legionella: Moving on From mip - Yong, Stacey F.; Tan, Shin Hwa; Wee, Joanne; Tee, Jing Jhi; Sansom, Fiona M.; Newton, Hayley J.; Hartland, Elizabeth L. (Frontiers in Microbiology, 2010)
The detection of Legionella pneumophila in environmental and clinical samples is frequently performed by PCR amplification of the mip and/or 16S rRNA genes. Combined with DNA sequencing, these two genetic loci can be used to distinguish different species of Legionella and identify L. pneumophila. However, the recent Legionella genome sequences have opened up hundreds of possibilities for the development of new molecular targets for detection and diagnosis. Ongoing comparative genomics has the potential to fine tune the identification of Legionella species and serogroups by combining specific and general genetic targets. For example, the coincident detection of LPS biosynthesis genes and virulence genes may allow the differentiation of both pathogen and serogroup without the need for nucleotide sequencing. We tested this idea using data derived from a previous genomic subtractive hybridization we performed between L. pneumophila serogroup 1 and Legionella micdadei. Although not yet formally tested, these targets serve as an example of how comparative genomics has the potential to improve the scope and accuracy of Legionella molecular detection if embraced by laboratories undertaking Legionella surveillance